2022
DOI: 10.2217/cer-2021-0311
|View full text |Cite
|
Sign up to set email alerts
|

Biologic initiation rates in systemic-naive psoriasis patients after first-line apremilast versus methotrexate use

Abstract: Aim: To compare rates of biologic initiation after commencing treatment with apremilast (APR) versus methotrexate (MTX) in systemic-naive patients with psoriasis (PsO). Methods: This was a retrospective cohort study of systemic-naive patients with PsO who initiated treatment with APR or MTX between 1 January 2015 and 31 March 2018. Outcomes: Adjusted rates of biologic initiation during follow-up were compared by logistic and Cox regressions. Results: APR initiators had 58% lower likelihood of biologic initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
1
0
1
Order By: Relevance
“…In a prior study (2005–2015), time from commencement of systemic therapy to the initiation of biologics was 6.8 years, which is in accordance with the 5.5 years of this study, but other studies have reported short time to biologics 8,9 . Surprisingly, we did not observe a decrease in time to first biologic therapy after introduction of biosimilars and observed a slight increase or no change at all.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In a prior study (2005–2015), time from commencement of systemic therapy to the initiation of biologics was 6.8 years, which is in accordance with the 5.5 years of this study, but other studies have reported short time to biologics 8,9 . Surprisingly, we did not observe a decrease in time to first biologic therapy after introduction of biosimilars and observed a slight increase or no change at all.…”
Section: Discussionsupporting
confidence: 91%
“…In a prior study (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015), time from commencement of systemic therapy to the initiation of biologics was 6.8 years, which is in accordance with the 5.5 years of this study, but other studies have reported short time to biologics. 8,9 Surprisingly, we did not observe a decrease in time to first biologic therapy after introduction of biosimilars and observed a slight increase or no change at all. The reasons for this remain unclear but could reflect that biologic therapies became more accessible to moderate disease severity who would otherwise have continued systemic treatment.…”
Section: Discussioncontrasting
confidence: 66%